Research Advances on Hepatotoxicity of Herbal Medicines in China. (18th December 2016) - Liu, Changxiao; Fan, Huirong; Li, Yazhuo; Xiao, Xiaohe
Abstract : In general, herbal medicines have been considered as safe by the general public, since they are naturally occurring and have been applied in treatment for over thousands of years. As the use of herbal medicine is rapidly increasing globally, the potential toxicity of herbal drugs, in particular drug-induced liver injury (DILI), has now become a serious medical issue. According to the literature, the authors analyzed and discussed the hepatotoxicity problem of Chinese herbal medicines (CHM), including global overview on herbal-induced liver injury (HILI), current research progress on toxic CHM, diagnosis and treatment of HILI, and modern approaches and technologies of study of hepatotoxicity. As to promote the recognition of HILI and tackle the issue, a guideline for the diagnosis and treatment of HILI has recently been drafted by Chinese scientists. As suggested by the guideline, the hepatotoxicity issue of CHM, as a matter of fact, is overestimated. Up to date, the investigation of hepatotoxicity of CHM is now booming with worldwide application of CHM. This review therefore provides useful information for investigating hepatotoxicity of herbal medicine and characterizing DILI caused by CHM. In addition, authors describe in which way further efforts should be made to study the rationale of CHM and liver injury.